Commodification in the Online Media Industry: Utilization of Users for Collaborative News Kumparan.com - Chrystelina Gustina Sitompul; Shantika Embundini Akbari (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2021)
Kumparan.com combines technology and innovation into the media by implementing technology-based journalism so that the news presented in Kumparan are not only written by Kumparan authors but also by users, readers, institutions and other stakeholders after being moderated by kumparan editors. This is what they call collaborative news. In collaborative news, Kumparan accepts articles from many people (User Generated Content) to fulfill its daily news production without having to hire and pay their wages, on the other hand, this makes Kumparan in the Top 10 Online Media Rankings on various surveys and research because of the amount of news and information coverage. When analyzed using Vincent Mosco's political economy perspective, the collaborative news format can be categorized as a practice of commodification, efforts made by the media to change everything in order to generate profits. This study uses a qualitative approach with research and interview methods to determine whether collaborative news is a practice of commodification carried out by Kumparan. The results of the study found that collaborative news contains elements of content/content and audience/audience commodification, where Kumparan innovates in news production by utilizing the audience without paying. Kumparan benefits materially from the presence of diverse content that increases traffic as an online medium without having to employ